Tingkat Pengetahuan Perawat Dan Penerapan Ventilator Associated Pneumonia Bundle Di Ruang Perawatan Intensif: Nurses' Knowledge Level and Implementation of Ventilator Associated Pneumonia Bundle in the Intensive Care Unit - Sri Idawati; Emil Huriani; Reni Prima Gusty (NERS Jurnal Keperawatan, 2017)
According to the Quality and Performance Report Benefits for Society Committee on Prevention and Control of Hospital Infection in 2014 found numerical Infections Ventilator Associated Pneumonia (VAP) 18.17 %, and in the last six months there were as many as 85.1% of patients in the ICU who use mechanical ventilation. Available protocol were not in accordance with the VAP bundle. Nurse was inconsistent in applying nursing intervention for VAP prevention. Research objective was to investigate orcrelation of knowledge of healthworkers with application of VAP prevention in ICU Hospital Dr. M. Djamil Padang. The research design was a descriptive cross sectional with total sample of 33 respondents. Analysis of the data by univariate and bivariate analysis. The results showed that 60 % of healthworkers had a high level of knowledge and 93.3 % of healthworkers performance in accordance with application of VAP Bundle. There was a significant relationship between knowledge level and the application of VAP Bundle in ICU (p= 0.001). Based on the research, suggested that the hospital is expected to provide variation or special training of nursing dissemination journal critical especially action mechanical ventilation so that the nurses can add insight into the latest knowledge of science so as to increase the quality of nurses. For management of room in order to establish SOP VAP Bundle to be always applied by the nurses in preventing the incidence of VAP.